Psychometric evaluation of a patient-reported outcomes instrument for congenital thrombotic thrombocytopenic purpura - Abiola Oladapo; Diane Ito; Ana María Rodriguez; Stephanie Philpott; Robert Krupnick; Veleka Allen; Christopher Hibbard; Marie Scully; Bruce Ewenstein (SpringerOpen, 2023)
Abstract Background Congenital thrombotic thrombocytopenic purpura (cTTP) is an ultra-rare, life-threatening hereditary disorder that causes patients to experience significant morbidity and decreased health-related quality of life (HRQoL). A cTTP disease-specific patient-reported outcome (PRO) instrument that is reflective of patients' experiences with the disorder does not currently exist. The objective of this study was to evaluate and validate the psychometric properties of the Congenital Thrombotic Thrombocytopenic Purpura-Patient Experience Questionnaire (cTTP-PEQ), developed using a literature review, interviews with expert clinicians, and qualitative concept elicitation and cognitive debriefing interviews. Methods This prospective, observational study (NCT03519672) was conducted with patients diagnosed with cTTP currently receiving treatment. Patients were enrolled through investigator sites and direct-to-patient recruitment. Individuals completed electronic self-administered PRO measures, including the cTTP-PEQ, at baseline and Day 14 (+ up to 10 days). The cTTP-PEQ consisted of five multi-item domains (Pain/Bruising, Cognitive Impairment, Visual Impairment, Mood, Treatment Burden) and three single-item domains (Fatigue, Headache, Activity Limitation), and assessed symptoms and impact of cTTP in the previous 24 h, 7 days, and 2 weeks. Convergent and discriminant validity were evaluated using Spearman's rank correlation coefficients. Known-groups validity was assessed between patient groups separated by Patient Global Impression of Severity (PGI-S; normal vs. mild/moderate/severe). Internal reliability was assessed using Cronbach's alpha. Test-retest reliability was assessed using intraclass correlation coefficients (ICCs). Results Thirty-six patients participated in this study. Convergent validity was confirmed with high-to-moderate correlations (r ≥ 0.4) for 12/15 hypothesized relationships between pairs of domains and/or total scores. Discriminant validity was confirmed with low correlations (r < 0.3) observed for 5/7 hypothesized relationships. Known-groups validity was confirmed with significant differences (p ≤ 0.05) in mean cTTP-PEQ scores between the two PGI-S groups for most domains and items at both timepoints. Cronbach's alpha was 0.88 at baseline and 0.91 at Day 14, confirming internal consistency of the instrument. Test-retest reliability was also confirmed with a high ICC (0.96). Conclusion This study validates the psychometric properties of the novel cTTP-PEQ for use in research and clinical practice to assess HRQoL among patients with cTTP. This instrument will be particularly useful when assessing cTTP disease burden and the impact of new treatments.